EFFICACY OF LOCAL VERSUS SPINAL ANAESTHESIA FOR MESH INGUINAL HERNIOPLASTY IN TERMS OF POSTOPERATIVE PAIN - Umerzai, Fahd Khalid; Kalim, Mohammad; Hussain, Mussarat (Journal of Postgraduate Medical Institute, 2016)
Objectives: To determine the efficacy of local versus spinal anaesthesia for mesh inguinal hernioplasty in terms to postoperative pain. Methodology: This study was conducted at Surgical D Unit, Lady Reading Hospital Peshawar. Study design was randomized control trial duration of the study was six months in which a total of 82 patients (41 in each group) were observed by using 79% proportion of pain in local7 and 99% proportion of pain in spinal7. 95% confidence level and 90% power of test under WHO software for sample size determination. More over non probability consecutive sampling technique was used for sample collection. Results: In this study mean age in Group A (local anaesthesia) was 30 ±6.47 years and in Group B (spinal anaesthesia) the mean age was 31 ±6.98 years. All the patients in both the groups were male. In Group A (local anaesthesia) 71% patients didn't had pain while 29% patients had pain. Where as in Group B (spinal anaesthesia) 61% patients didn't had pain and 39% patients had pain. Hence on the basis of pain local anaesthesia was effective in 71% patients and spinal anaesthesia was effective in 61% patients. Conclusion: Local anaesthesia was more effective than spinal anaesthesia for mesh inguinal hernioplasty in terms of postoperative pain.